A comparison of the effectiveness of EFL students' use of dictionaries and an online corpus for the enhancement of revision skills. Issue 1 (26th August 2015) - Mueller, Charles M.; Jacobsen, Natalia D.
Abstract: Qualitative research focusing primarily on advanced-proficiency second language (L2) learners suggests that online corpora can function as useful reference tools for language learners, especially when addressing phraseological issues. However, the feasibility and effectiveness of online corpus consultation for learners at a basic level of L2 proficiency have been relatively unexplored. The current study of Japanese-L1 (first language) learners in an EFL (English as a foreign language) context ( N =117) addresses these gaps in research. A preliminary investigation (Experiment 1) examined EFL learners ( n =78) as they used the Corpus of Contemporary American English (COCA: Davies, 2008 –) to revise essays. Experiment 2 ( n =39) used a within-subjects comparison to determine whether participants attained greater accuracy in supplying the missing word in a gap-fill test when using an electronic dictionary or COCA. The survey results from the two experiments revealed that participants generally found using an online corpus difficult. In Experiment 2, a paired-samples t -test showed that participants, at an alpha of p =.05 two-tailed, were marginally better able to answer test questions when using the online corpus than they were when using an electronic dictionary, p =0.030. The implications of the study within the context of previous research are discussed along with pedagogical recommendations and possible avenues for future research.